New Patronage Networks of Pemuda Pancasila in Governor Election of North Sumatra In 2013 (International Journal of Scientific Research and Management (IJSRM), 2018)
This research is motivated by the emergence of the "thugs" as local actors in North Sumatra that play a role in supporting Gatot Pudjonugroho as a candidate for Governor of North Sumatra. The majority of local actors were coming from a cadre of Pemuda Pancasila. They do not just rely on violence and money owned, but they have a network to rulers in the region. They can use that capacity to gain access to the resources of the local government and maximize the power network owned. The main theory is used Bossism theory of John T. Sidel and Group Violence written by Masaaki and Rozaki. A case study approach and qualitative analysis and typology chosen as a way to draw up a written interpretation of the data, interview and observation. The findings show that a form of intimidation by members of the Pemuda Pancasila is threatening physical beatings and create inconvenience voters who did not vote candidate supported. The pattern of mobilization on the basis of patron-client pyramid. Model relationship that exists between the Pemuda Pancasila with the bureaucracy, businessmen, and local print media carried out on symbiotic mutualism. The phenomenon appears and the persistence of local bosses and violent groups identify their distinctive differences in North Sumatra. A contribution to Political Science theory perspective found in this study is called Theory of New Patronage Network of Local Boss